Identifying barriers in the field of electronic payments based on blockchain technology: A multi-criteria decision-making approach - Amir Mohammad Yektaei Rudsari; Naser Safaei; Majid Mirzaei Ghazani (مدیریت مهندسی و رایانش نرم)
With the growing trend of electronic payments, the use of blockchain technology has been introduced as one of the solutions for safe money transfer. Some of these obstacles include technical, technological, organizational, financial and security problems. To identify and prioritize these obstacles and solve them, multi-criteria decision-making methods can be useful.In this research, in order to identify and rank the factors of obstacles related to electronic payments based on blockchain technology, the Delphi method has been used. This method includes reading previous articles and collecting the opinions of 35 specialists and experts in this field. To analyze the relationship between the factors and identify their causal relationships, the Dimtel method was used and finally, to prioritize the factors, the process of network analysis was used.Out of 13 indicators, 11 indicators were evaluated in the final analysis. The privacy compliance index has the greatest impact on other indicators. On the other hand, indicators of non-commitment and the desire of senior managers to improve and make fundamental changes are also more influential than other indicators.